Analysis of the Effectiveness of Zakat Management in Poverty Alleviation: A Comparative Study of Indonesia and Malaysia - Siti Maulidia; Siti Nur Latifah; Raihan Nasir (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Introduction: This study aims to analyze the effectiveness of zakat fund management in reducing poverty in Indonesia and Malaysia during the 2015–2025 period. The study is motivated by a theoretical gap regarding the role of zakat as an instrument for poverty alleviation, which in practice shows different results across countries. Methods: This research employs a quantitative approach using linear regression analysis with the assistance of the EViews application. The regression estimation method applied in this study is the Ordinary Least Square (OLS) method. The data used in this study consist of secondary data on zakat collection and poverty levels in Indonesia and Malaysia during the observation period. Results: The results show that zakat in Indonesia has a negative and significant effect on poverty, while in Malaysia zakat has a negative but insignificant effect on poverty. Based on the R-square value, zakat management in Indonesia is more effective in reducing poverty than in Malaysia. These findings indicate that the optimization of productive zakat distribution is able to improve community welfare more effectively. Conclusion and suggestion: Zakat institutions should strengthen productive zakat programs, improve management efficiency, and enhance collaboration with relevant stakeholders to maximize the role of zakat in poverty reduction. Future research may include additional variables and broader country coverage to provide more comprehensive results.